Tunable Dielectric and Microwave Properties of Epoxy Composites with Cofe2o4 and Mgfe2o4 Spinel Ferrites - Casagrande-Denardin, J (SPRINGER HEIDELBERG, 2025)
In this study, we developed polymer-ceramic composites based on diglycidyl ether bisphenol A (DGEBA) epoxy resin reinforced with spinel ferrites, CoFe2O4 (CFO) and MgFe2O4 (MFO), aiming for advanced dielectric applications. The curing process was optimized using branched polyethyleneimine (BPEI) as a hardener, achieving an optimal 4:1 DGEBA: BPEI ratio at 100 degrees C for 1 h. Structural and morphological characterizations were performed using XRD, vibrating sample magnetometry (VSM), FTIR and SEM. Dielectric properties were investigated through impedance spectroscopy in the radiofrequency range (1-10 MHz) at temperatures from 100 to 200 degrees C, while microwave properties were analyzed in the X-band (8.2-12.4 GHz). All analyzed samples exhibited behavior that could be described by two R-CPE circuits. The composites were also evaluated in the microwave region, specifically in the X-band, where two absorption peaks were observed at around 11 and 11.9 GHz for the MFO10, MFO20, and CFO10 samples.